Guerra-Peixe’s Symphony No. 2 Brasília (Part 2): a musical analysis (Per Musi, 2018)
The present article presents a broad musical analysis of the Symphony No. 2 Brasília by Brazilian composer César Guerra-Peixe, covering formal, melodic, motivic and harmonic aspects. The terminology of the analytical terms was the same used by Peter Brown in his five volume series of all representative symphonies of the symphonic literature. These terms came from Guidelines to Style Analysis by Jan LaRue. The Symphony Brasília was subject of my doctoral project in three principal fronts: production of a performance edition of the full score and parts; performance of the work in the US and Brazil, aiming to correct eventual mistakes and spread the music; and a production of historical and analytical texts. The present article will cover the musical analysis. A previous article covered historical aspects of the work.